Persepsi Followers Terhadap Konten Perayaan Hari Peduli Sampah Nasional Pada TikTok Pandawara Group - Nufus, Qonningatun; Sukmawati, Ade Irma (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2024)
TikTok is a popular social media platform and has become a place for users to share. The popularity of Tiktok social media can be a forum for Indonesian content creators to be creative and have a positive influence on their followers. The aim of this research is to find out how followers perceive the content celebrating National Waste Awareness Day shared by the Tiktok Pandawara Group account using the basis of stimulus-organism-response (S-O-R) theory. The approach to this research uses a descriptive quantitative approach using a positivistic paradigm and survey methods. The sampling technique used was purposive sampling with a total sample of 280 respondents. The calculated results for the reliability test were 0.919, the validity test was 0.772 and the correlation test was 0.654. The results of the research show that followers' perceptions of the National Waste Day Celebration content on the Pandawaragroup Tiktok account are positive. This is in accordance with the assumptions of the Stimulus-Organism-Response theory depicted in this research, where the stimulus in the form of National Waste Awareness Day video content provided can be well received by followers.